2017
DOI: 10.31236/osf.io/dxqng
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Empathic and Self-Regulatory Processes Governing Doping Behavior

Abstract: Evidence associating doping behavior with Moral Disengagement (MD) has accumulated over recent years. However, to date, research examining links between MD and doping has not considered key theoretically-grounded influences and outcomes of MD. As such, there is a need for quantitative research in relevant populations that purposefully examines the explanatory pathways through which MD is thought to operate. Towards this end, the current study examined a conceptually-grounded model of doping behavior that incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
4
13
0
Order By: Relevance
“…In their seminal study, Bandura, Barbaranelli, Caprara, and Pastorelli (1996) found that anticipated guilt negatively predicted aggressive behavior in school children. Similar results have been reported in relation to Doping Likelihood athletes' antisocial behavior (e.g., Stanger, Kavussanu, Boardley, & Ring, 2013) as well as their doping likelihood and susceptibility (e.g., Boardley et al, 2017;Kavussanu & Ring, 2017;Ring & Kavussanu, 2018). Other anticipated negative emotions such as regret or shame about potential doping have also been negatively associated with doping intentions in adolescent and adult athletes (Barkoukis, Lazuras, & Harris, 2015;Lazuras, Barkoukis, & Tsorbatzoudis, 2015).…”
Section: Moral Variables and Dopingsupporting
confidence: 79%
“…In their seminal study, Bandura, Barbaranelli, Caprara, and Pastorelli (1996) found that anticipated guilt negatively predicted aggressive behavior in school children. Similar results have been reported in relation to Doping Likelihood athletes' antisocial behavior (e.g., Stanger, Kavussanu, Boardley, & Ring, 2013) as well as their doping likelihood and susceptibility (e.g., Boardley et al, 2017;Kavussanu & Ring, 2017;Ring & Kavussanu, 2018). Other anticipated negative emotions such as regret or shame about potential doping have also been negatively associated with doping intentions in adolescent and adult athletes (Barkoukis, Lazuras, & Harris, 2015;Lazuras, Barkoukis, & Tsorbatzoudis, 2015).…”
Section: Moral Variables and Dopingsupporting
confidence: 79%
“…This indirect pathway suggests that the greater the perceived capacity to resist temptation the less mechanisms of moral disengagement are used to justify unethical conduct. Recent research has provided evidence to support this indirect pathway in the context of doping (e.g., Boardley et al, 2017;Corrion et al, 2017;Kavussanu & Ring, 2017;Ring & Kavussanu, 2018a). The current study evaluated this pathway in situations associated with potential benefits and costs for the athlete.…”
Section: Doping and Social Cognitive Theorymentioning
confidence: 96%
“…This study is the first to link athlete perceptions of coach DCE with outcomes relevant to both intentional and inadvertent doping, building upon the dominant focus on intentional doping . We also extended the predominant focus on technical coaches to consider strength and conditioning coaches, who work within environments where doping is prevalent . In also identifying potential psychosocial processes linking athletes' perceptions of their coaches with doping outcomes and demonstrating replicability of the proposed model by sex and across athletes from three continents, this work offers several meaningful advancements to the doping knowledge base.…”
Section: Discussionmentioning
confidence: 89%
“…Then, through vicarious influence, a coach demonstrating such behavior may enhance athlete doping SRE, which theoretically should tie with reduced doping MD as athletes who feel more confident in their ability to resist pressures and risks to dope should have lesser need to justify and rationalize doping . This possibility that changes in MD explain links between SRE and doping has previously been supported for self‐reported doping …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation